Penerapan Omnichannel Untuk Caring Pelanggan Indihome Pada Customer Care Telkom Witel Bandung - Rahayu Adha Putri; Hadi Purnama (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This study aims to find out and describe the application of omnichannel for IndiHome customer caring programs carried out by the customer care unit from a digital public relations perspective, because to build long-term relationships to maintain customer loyalty is Customer Relations which is one of the Public Relations activities. The research uses a qualitative approach with a constructivism paradigm to find meaning in an event or activity through interviews and observation, and the case study method. Based on the results of this study, the implementation of omnichannel by customer care through various digital media, namely telephone, email, Whatsapp, dashboard Omnichannel Communication Assistant, and Online Integrated Notification focuses on building customer engagement and increasing customer loyalty, and refers to the goals set based on the company's customer journey which are integrated. The problems experienced during the customer caring program in the form of telephone rejection, messages not being answered, and invalid customer data. So that the evaluation is carried out by the customer care unit through reports, Net Promoter Score results, and the results of successful complaint handling.